Taxonomic diagnosis of Dicyrtomina ornata and D. saundersi (Collembola: Dicyrtomidae) and analysis of their population genetic structure - Fanciulli, Pietro Paolo; Belloni, Massimo; Carapelli, Antonio; Dallai, Romano; Frati, Francesco (Zenodo, 2001)
Fanciulli, Pietro Paolo, Belloni, Massimo, Carapelli, Antonio, Dallai, Romano, Frati, Francesco (2001): Taxonomic diagnosis of Dicyrtomina ornata and D. saundersi (Collembola: Dicyrtomidae) and analysis of their population genetic structure. Zootaxa 10: 1-16 : {"references": ["Ambrosetti, P., Carboni, M.G., Conti, M.A., Costantini, A., Esu, D., Gandin, A., Girotti, O., Lazzarotto, A., Mazzanti, R., Nicosia, U., Parisi, G. & Sandrelli, F. (1978) Evoluzione paleogeografica e tettonica nei bacini Tosco-Umbro-Laziali nel Pliocene e nel Pleistocene inferiore. Memorie della Societa Geologica Italiana, 19, 573-580.", "Bellinger, P.F. & Christiansen, K. (1989) Biogeography of the Collembola of Hawaii. In: Dallai, R., (Ed) Third International Seminar on Apterygota, University of Siena, Siena, pp. 121-126.", "Betsch, J.-M. (1980) Elements pour une monographie des collemboles Symphypleones (Hexapodes, Apterygotes). Memoires du Museum National d'Histoire Naturelle, 116A, 1-127.", "Bohonak, A.J., Davies, N., Roderick, G.K. & Villablanca, F.X. (1998) Is population genetics mired in the past? Trends in Ecology and Evolution, 13, 360.", "Bossart, J.L. & Prowell, D.P. (1998) Genetic estimates of population structure and gene flow: limitations, lessons and new directions. Trends in Ecology and Evolution, 13, 202-206.", "Bretfeld, G. (1999) Synopses on Palaearctic Collembola - Symphypleona. Abhandlungen und Berichte des Naturkundemuseums Gorlitz, 71, 1-318.", "Carapelli, A., Fanciulli, P.P., Frati, F. & Dallai, R. (1995a) The use of genetic markers for the diagnosis of sibling species in the genus Isotomurus (Insecta, Collembola). Bollettino di Zoologia, 62, 71-76.", "Carapelli, A., Frati, F., Fanciulli, P.P. & Dallai, R. (1995b) Genetic differentiation of six species of Isotomurus (Collembola, Isotomidae); is there any difference in their microhabitat preference? European Journal of Soil Biology, 31, 87-99.", "Cassagnau, P. (1987) A propos des types de coloration chez Isotomurus palustris (Muller) (Collemboles). Revue d'Ecologie et Biologie du Sol, 24, 85-89.", "Chiba, S. (1998) Genetic variation derived from natural gene flow between sympatric species in land snails (Mandarina). Heredity, 80, 617-623.", "Christiansen, K. (1964) Bionomics of Collembola. Annual Review of Entomology, 9, 147-178.", "Cobolli Sbordoni, M., Ketmaier, V., De Matthaeis E. & Taiti, S. (1997) Biochemical systematics and evolutionary relationships in the Trichoniscus pusillus complex (Crustacea, Isopoda, Oniscidea). Heredity, 79, 463-472.", "Dallai, R., Fanciulli P.P. & Petrucci, R.(1985) Enzyme diversity in the genus Bilobella (Insecta, Collembola). Revue d'Ecologie et Biologie du Sol, 25, 365-372.", "Deharveng, L. & Bedos, A. (1991) Taxonomy and cladistics analysis of the Thai species of Friesea Dalla Torre 1895 (Collembola, Neanuridae). Tropical Zoology, 4, 287-315.", "Deharveng, L., Bedos, A. & Gisclard C. (1998) Environmental factors, microgeographic patterns of endemism and hybrid zones in Monobella grassei (Insecta: Collembola: Neanuridae). Biological Journal of the Linnean Society, 64, 527-554.", "Fanciulli, P.P., Gaju, M, Bach, C. & Frati F. (1997) Genetic differentiation and detection of cryptic species in the genus Lepismachilis (Insecta: Microcoryphia) from the Western Mediterranean region. Biological Journal of the Linnean Society, 62, 533-551.", "Fanciulli, P.P., Melegari, D., Carapelli, A., Frati, F. & Dallai, R. (2000) Population structure, gene flow and evolutionary relationships in four species of the genera Tomocerus and Pogonognathellus (Collembola, Tomoceridae). Biological Journal of the Linnean Society, 70, 221-238.", "Fanciulli, P.P., Summa, D., Dallai, R. & Frati, F. (2001) High levels of genetic variability and population differentiation in Gressittacantha terranova (Hexapoda, Collembola) from Victoria Land, Antarctica. Antarctic Science, 13, 245-253.", "Farrow, R.A. & Greenslade, P. (1992) A vertical migration of Collembola. Entomologist, 111, 38- 45.", "Frati, F., Fanciulli, P.P. & Dallai, R. (1992) Genetic diversity and taxonomy in soil dwelling insects: the genus Orchesella, The Journal of Heredity, 83, 275-281.", "Frati, F., Dell'Ampio, E., Casasanta, S., Carapelli, A. & Fanciulli, P.P. (2000) Large amounts of genetic divergence among Italian populations and species of the genus Orchesella (Insecta, Collembola) and the relationships of two new species. Molecular Phylogenetics and Evolution, 17, 456-461.", "Gentile, G. & Sbordoni, V. (1998) Indirect methods to estimate gene flow in cave and surface populations of Androniscus dentiger (Isopoda: Oniscidea). Evolution, 52, 432-442", "Gisin, H. (1960) Collembolenfauna Europas, Museum d'Histoire Naturelle, Geneve, 312 pp.", "Goulson, D. (1993) Allozyme variation in the butterfly, Maniola jurtina (Lepidoptera: Satyrinae) (L.): evidence for selection. Heredity, 71, 386-393.", "Hagvar, S. (1995) Long distance, directional migration on snow in a forest collembolan, Hypogastrura socialis (Uzel). Acta Zoologica Fennica, 196, 200-205.", "Hanski, I. (1998) Metapopulation dynamics. Nature, 396, 41-49.", "Hopkin, S.P. (1997) Biology of Springtail (Insecta Collembola). Oxford University Press, Oxford, 330 pp.", "Johnson, M. S. & Black, R. (1998) Increased genetic divergence and reduced genetic variation in populations of the snail Bembicium vittatum in isolated tidal ponds. Heredity, 80, 163-172.", "Kimura, M. (1983) The Neutral Theory of Molecular Evolution. Cambridge University Press, Cambridge, 367 pp.", "King, K.L., Greenslade, P. & Hutchinsons, K. J. (1985) Collembolan association in natural versus improved pastures of the New England Tableland, NSW: distribution of native and introduced species. Australian Journal of Ecology, 10, 421-427.", "Lewontin, R. C. (1991) Twenty-five years ago in genetics:electrophoresis in the development of evolutionary genetics: milestone or millstone? Genetics, 128, 657-662.", "Mantel, N. (1967) The detection of desease clustering and a generalized regression approach. Cancer Research, 27, 209-220", "Mantovani, E., Albarello, D., Babbucci, D. & Tamburelli, C. (1992) Recent Geodynamic Evolution of the Central Mediterranean Region. Universita di Siena, Siena, 88 pp.", "Mayr, E. (1963) Animal Species and Evolution. Harvard University press, Cambridge, 797 pp.", "Miller, M.P. (1999) MANTEL-STRUCT: a program for the detection of population structure via mantel tests. Journal of Heredity, 90, 258-259", "Murphy, R.F., Sites, J.W.Jr., Buth, D.G. & Haufler, C.H. (1996) Proteins I: isozyme electrophoresis. In: Hillis D.M., Moritz, C. & Mable, B.K. (Ed) Molecular Systematics, Sinauer, Sunderland MA, pp. 51-120.", "Nei, M. (1972) Genetic distance between populations. American Naturalist, 106, 283-292.", "Nei, M. (1978) Estimation of average heterozygosity and genetic distance from a small number of individuals. Genetics, 89, 583-590.", "Neigel, J.E. (1997) A comparison of alternative strategies for estimating gene flow from genetic markers. Annual review of Ecology and Systematics, 28, 105-128.", "Poinsot-Balaguer, N. (1972) Etude systematique et ecologique des collemboles Isotomidae de Provence. Annales de la Societe Entomologique de France, 8, 669-691.", "Richards, W.R. (1968) Generic classification, evolution and biogeography of the Sminthuridae of the World (Collembola). Memoirs of the Entomological Society of Canada, 53, 1-54.", "Rogers, J.S. (1972) Measures of genetic similarity and genetic distance. Studies in genetics, University of Texas Pubblication, 7213, 145-153.", "Salmon, J.T. (1964) An index to the Collembola. Royal Society of New Zealand Bulletin, 7, 1-651.", "Simonsen, V., Filser, J., Henning Krogh, P. & Fjellberg A. (1999) Three species of Isotoma (Collembola, Isotomidae) based on morphology, isozymes and ecology. Zoologica Scripta, 28, 281- 287.", "Skibinski, D.O.F., Woodwark, M. & Ward, R.D. (1993) A quantitative test of the neutral theory using allozyme data. Genetics, 135, 233-248.", "Slatkin, M. (1985) Rare alleles as indicators of gene flow. Evolution, 39, 53-65.", "Slatkin, M. & Barton, N.H. (1989) A comparison of three indirect methods for estimating average levels of gene flow. Evolution, 43, 1349-1368.", "Sneath, P.H.A. & Sokal, R.R. (1973) Numerical Taxonomy. W.H. Freeman, San Francisco, 573 pp.", "Stach, J. (1957) The Apterygotan Fauna of Poland in Relation to the World Fauna of This Group of Insects. Families Neelidae and Dicyrtomidae. Polska Akademia Nauk Instytut Zoologiczny, Krakow, 113 pp.", "Swofford, D.L. & Berlocher, S.H. (1987) Inferring evolutionary trees from gene frequency data under the principle of maximum parsimony. Systematic Zoology, 36, 293-325.", "Swofford, D.L. & Selander, R.B. (1981) BIOSYS-1: a FORTRAN program for comprehensive analysis of electrophoretic data in population genetics and systematics. Journal of Heredity, 72, 281-283.", "Whitlock, M.C. & McCauley, D.E. (1999) Indirect measures of gene flow and migration: Fst 1/ (4Nm+1). Heredity, 82, 117-125.", "Wright, S. (1931) Evolution in mendelian populations. Genetics, 16, 97-159.", "Yoshii, R. (1989) On some Collembola of New Caledonia, with notes on the color pattern of the species. Contributions from the Biological Laboratory, Kyoto University, 27, 233-259."]}